Konflik dan Harmonisasi Regulasi Hak Atas Tanah Laut: Studi Kasus Penataan Wilayah Pesisir dan Pulau-Pulau Kecil - Johamran Pransisto; Lilis Suryani; Andi Heridah; Saharuddin Saharuddin; Dewi Rasda; Eka Novianty Wahyuni (Jurnal Litigasi Amsir, 2025)
This study discusses conflicts and harmonization of regulations on marine land rights in the context of the arrangement of coastal areas and small islands in Indonesia. The main problems identified are the overlap of authority between agencies and the unclear boundaries of jurisdiction, which have an impact on legal uncertainty, losses to coastal communities, and threats to environmental sustainability. The research uses normative methods with a legislative approach and literature analysis to identify the root of the problem and formulate a harmonization strategy. The results of the study show that policy integration, the formation of cross-ministerial teams, and the preparation of integrated norms, standards, procedures, and criteria (NSPK) are strategic steps to overcome regulatory conflicts and realize fair and sustainable coastal governance.